1997
DOI: 10.1002/elps.1150181114
|View full text |Cite
|
Sign up to set email alerts
|

Nonenzymatic chemiluminescent detection and quantitation of total protein on Western and slot blots allowing subsequent immunodetection and sequencing

Abstract: We have studied the light emission efficiency of proteins labeled with different fluorescent dyes chemically excited by the bis(2,4,6-trichlorophenyl)oxalate (TCPO)-H2O2 reaction. Using this peroxyoxalate chemiluminescence system, the best results were obtained with proteins covalently labeled with 2-methoxy-2,4-diphenyl-3(2H)-furanone (MDPF). Blotted proteins on polyvinylidene difluoride (PVDF) membranes can be labeled rapidly with MDPF. Our results demonstrate that energy from the excited intermediate produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 29 publications
1
16
0
Order By: Relevance
“…For the fluorescence detection, the wet membrane was placed onto an UV transilluminator (302 nm) and photographed using the Gel Doc 1000 system (equipped with the 590DF100 filter; f/1; exposure time 0.5-0.7 s) from Bio-Rad. After fluorescence imaging, the membrane was allowed to dry in air before proceeding to chemiluminescence detection, following a procedure previously described for fluorophore-labelled proteins on PVDF membranes (9). The blot was then laid over a Whatman 3MM paper and placed in a transparent plastic bag.…”
Section: Detection Of Dna On Membranesmentioning
confidence: 99%
See 1 more Smart Citation
“…For the fluorescence detection, the wet membrane was placed onto an UV transilluminator (302 nm) and photographed using the Gel Doc 1000 system (equipped with the 590DF100 filter; f/1; exposure time 0.5-0.7 s) from Bio-Rad. After fluorescence imaging, the membrane was allowed to dry in air before proceeding to chemiluminescence detection, following a procedure previously described for fluorophore-labelled proteins on PVDF membranes (9). The blot was then laid over a Whatman 3MM paper and placed in a transparent plastic bag.…”
Section: Detection Of Dna On Membranesmentioning
confidence: 99%
“…We have previously shown that the TCPO-H 2 O 2 reaction can be used for the detection of fluorophorelabelled proteins in solution and on polyvinylidene difluoride (PVDF) membranes (9). In the case of double-stranded DNA, however, we have found that the intercalation of different fluorescent labels between DNA bases inhibits peroxyoxalate chemiluminescence (10).…”
Section: Introductionmentioning
confidence: 97%
“…Following transfer, blots were labeled with MDPF essentially as described previously [17]. Blots were equilibrated twice (for 5 rnin each time) in 100 mL of 10 mM sodium borate, pH 9.5.…”
Section: Mdpf Labeling Of Proteins On Membranementioning
confidence: 99%
“…Stained protein bands to be sequenced were marked with a soft pencil while the membrane was UV-transilluminated; the selected bands were cut out of the membrane and applied to an LF3000 Automatic Sequencer (Beckman, Palo Alto, CA, USA). For comparative purposes, a duplicate of the blot was stained with Coomassie blue as described elsewhere [17] and protein bands were also cut out of the PVDF membrane for N-terminal sequence analysis.…”
Section: Immunodetection and N-terminal Sequencingmentioning
confidence: 99%
“…To eliminate the risk of missing or misrepresenting levels of proteins that do not blot well, Smejkal et al [13] developed a CL-based method which directly immunodetected proteins in agarose gels by conventional antibodybased procedures, and not on electroblots. In addition, CL detection of total protein profiles has also been reported [14,15], which is based on the CL signals from proteins labeled with the fluorescent reagent 2-methoxy-2,4-diphenyl-3(2H)-fluranone (MDPF), but the procedure of electroblotting to PVDF membranes cannot be eliminated. Because of the high cost of antibodies and the risk of missing proteins during transferring procedures, it is of great importance to develop new methods to detect proteins without transfer and immunoreaction.…”
Section: Introductionmentioning
confidence: 99%